2022
DOI: 10.1051/0004-6361/202143006
|View full text |Cite
|
Sign up to set email alerts
|

TRAPUM discovery of 13 new pulsars in NGC 1851 using MeerKAT

Abstract: We report the discovery of 13 new pulsars in the globular cluster NGC 1851 by the TRAPUM Large Survey Project using the MeerKAT radio telescope. The discoveries consist of six isolated millisecond pulsars (MSPs) and seven binary pulsars, of which six are MSPs and one is mildly recycled. For all the pulsars, we present the basic kinematic, astrometric, and orbital parameters, where applicable, as well as their polarimetric properties, when these are measurable. Two of the binary MSPs (PSR J0514−4002D and PSR J0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…These nondetections can be explained because we do not yet have a phase-coherent timing solution, but also because of the difference of sensitivity of the MeerKAT, GBT, and GMRT observations. The survey sensitivity of TRAPUM GC observations for NGC 1851 has been reported previously in Section 2.1 of Ridolfi et al (2022) using the modified radiometer equation (Dewey et al 1985). Adjusting these numbers for the values reported in Table 1 for TRAPUM observations of M30, we get a minimum detectable flux density of 14.1 μJy at the L band and 19.9 μJy at the UHF band compared to 109.3 μJy for the 400 MHz GMRT observation of M30 reported in Gautam et al (2022).…”
Section: Pulsar Timingsupporting
confidence: 57%
See 1 more Smart Citation
“…These nondetections can be explained because we do not yet have a phase-coherent timing solution, but also because of the difference of sensitivity of the MeerKAT, GBT, and GMRT observations. The survey sensitivity of TRAPUM GC observations for NGC 1851 has been reported previously in Section 2.1 of Ridolfi et al (2022) using the modified radiometer equation (Dewey et al 1985). Adjusting these numbers for the values reported in Table 1 for TRAPUM observations of M30, we get a minimum detectable flux density of 14.1 μJy at the L band and 19.9 μJy at the UHF band compared to 109.3 μJy for the 400 MHz GMRT observation of M30 reported in Gautam et al (2022).…”
Section: Pulsar Timingsupporting
confidence: 57%
“…However, the extreme stellar densities at the cores of the GCs with the highest interaction rates per binary, γ (Verbunt & Freire 2014)-especially the core-collapsed GCs-imply that stars are likely to go through repeated gravitational interactions with other stars and binaries in the core. This leads to the formation, in these GCs, of binary systems where already fully recycled MSPs acquire massive companions in additional exchange encounters (Prince et al 1991;Freire et al 2004;Lynch et al 2012;DeCesar et al 2015;Ridolfi et al 2021Ridolfi et al , 2022Kremer et al 2022). If these massive companions are degenerate, these orbits retain the high eccentricity of the systems after the exchange encounters.…”
Section: Introductionmentioning
confidence: 99%
“…These Γ values mean that LMXBs and MSP binaries should form in 𝜔-Cen at a rate ∼ 7 times smaller than that of 47 Tuc. However, the 18 pulsars in 𝜔-Cen are two thirds of the 27 pulsars detected in 47 Tuc with the same telescope (MeerKAT) and receivers (L-band, see Ridolfi et al 2021). This is partly a result of the fact that the latter searches were done only with a single beam using 44 antennas within the 1-km core, not all 64 antennas and many hundreds of beams as the search described here; however this difference is in part compensated by the larger distance of 𝜔-Cen (5.2 kpc) compared to 47 Tuc (4.5 kpc).…”
Section: Why This Pulsar Population Is Surprisingmentioning
confidence: 99%
“…About one-third of these (e.g. Ridolfi et al 2021;Douglas et al 2022;Ridolfi et al 2022;Vleeschower et al 2022;Abbate et al 2022), are found in various GCs, including 47 Tucanae (Chen et al, in prep. ), a cluster that has been searched for over 20 years.…”
Section: The Meerkat Surveymentioning
confidence: 99%
See 1 more Smart Citation